ANALYSIS OF THE EFFECT OF SHARIA BANK INDONESIA CERTIFICATES, MONEY SUPPLY, INFLATION, AND RUPIAH EXCHANGE RATE ON SHARIA MUTUAL FUNDS IN INDONESIA - Nurul Hikmah; Sri Astuty; Basri Bado (Nurul Jadid University, 2025)
This study aims to analyse how SBIS, JUB, Inflation and Rupiah Exchange Rate affect Islamic Mutual Funds in Indonesia using the VECM method. Using EVIEWS 12 software, this study analysed 96 data within a period of 8 years published during the period January 2017 to December 2024 relating to the topic. The results show that in the long run, JUB and Rupiah Exchange Rate have a significant positive effect, SBIS has a significant negative effect while inflation has no effect. In the short term, Inflation has a significant negative effect while SBIS, JUB, and Rupiah Exchange Rate have no significant effect on Islamic Mutual Funds in Indonesia.